The Catholic Meaning Behind The Name: Name Management Analysis - Sanga, Laurensius Dihe; Balun, Bernardus Somi (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2024)
This writing aims to assert that not just anyone can use the name